Misrepresentation of Russian Interests in the Russo–Ukrainian War: The Closure of News Offices in Russia - Julia Magdalena Wuysang; Ira Patriani; Netty Herawati (Technium Social Sciences Journal, 2023)
The misrepresentation of Russian interests in the ongoing Russo–Ukrainian War has drawn extensive public criticism. Scholars have investigated the war between Russia and Ukraine using diverse perspectives and using various aspects. Few, however, have examined the mechanisms through which Russian interests have been misrepresented. This article, thus, uses media analysis to investigate the Russo–Ukrainian War, relying on a review of the literature (previous studies, books, and digital news articles) to obtain its data. This study of the misrepresentation of Russian interests in the Russo–Ukrainian War finds 1) American and Ukrainian media have highlighted the disarray of the Russian offensive; 2) the media has misrepresented Russia’s interests; 3) Russia and Ukraine have presented different information regarding the Russia–Ukraine War; 4) throughout the Russo–Ukrainian War, Russia has employed a DIME (Diplomacy, Information, Military, and Economy) strategy for its international politics. This study contributes to an understanding of the misrepresentation of Russia’s interests on social media during the Russo–Ukrainian War.